2020
DOI: 10.1051/e3sconf/202020804010
|View full text |Cite
|
Sign up to set email alerts
|

The level of railway rates as a factor of sustainable development of territories

Abstract: This article attempts to assess the impact of the level of railway rates on the sustainable development of territories (on the example of Russia, freight and passenger rates, 2000-2018) using econometric modeling with an autoregressive model. As follows from the results obtained, in general, the statistically significant effect of the level of railway rates on the sustainable development of territories can be identified only for some indicators that assess certain aspects of sustainable development. Evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A number of works by modern scientists and economists such as Y. Egorov, N. Zhuravleva, M. Poliak, V.A. Manova, A.S. Lebedeva, C. Blanquart, M. Koning and others, confirm that the use of high-speed trains for freight transportation is very promising [2][3][4], but the presence of the following infrastructure limitations is revealed:…”
Section: The Results Of the Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A number of works by modern scientists and economists such as Y. Egorov, N. Zhuravleva, M. Poliak, V.A. Manova, A.S. Lebedeva, C. Blanquart, M. Koning and others, confirm that the use of high-speed trains for freight transportation is very promising [2][3][4], but the presence of the following infrastructure limitations is revealed:…”
Section: The Results Of the Analysismentioning
confidence: 99%
“…Based on the results of the literature analysis [2][3][4][5], it can be concluded that the main type of problems hindering the development of the high-speed freight transportation market consists in technical and technological barriers, and the lack of full and timely financing of development projects in progress.…”
Section: The Results Of the Analysismentioning
confidence: 99%
“…The parameters of modeling the demand for rail transportation, taking into account structural changes affecting the activities of the main sectors of the national economy [11], can significantly improve the analytical base for the development of freight forecasts. In general, a significant amount of research indicates the importance of finding optimal solutions when predicting the volume and structure of cargo transportation in the current instability of the transport services market and numerous logistical sanctions restrictions [12,13].…”
Section: Discussionmentioning
confidence: 99%